Teknologi ANALISIS SIFAT MEKANIK MECANUM WHEEL PADA MOTO TUG HELIKOPTER BELT 412 EPI BERBASIS ELEKTRIK: Otoranpur (Jurnal Otoranpur, 2022)
Abstract: Developments in the world of technology are growing rapidly, especially in the military field. This is evidenced by the increasing number of various and increasingly modern defense equipment systems. Various countries compete with each other to strengthen their military, this military rivalry has existed since the kingdom era with the aim of developing technology that is driven by the desire and need to provide a sense of security for their country. The development of this technology is not only for military weapons but in the world of military aviation also requires a tool that can be used as a tool in the process of moving helicopters, especially the Bell 412EPI helicopter. The Bell 412EPI Helicopter is a helicopter belonging to the Indonesian National Army, especially from the Army Pilot. The BellL 412EPI has stronger power and the Bell 412EPI avionics already uses a full glass cockpit. The Belll 412EPI helicopter is a defense equipment that has the ability to carry 15 people with 1 pilott and 14 ppassengers. The helicopter is equipped with a Pratt & Whitney PT6T-9 Twin Pac engine, with 15 percent more take-off power than other Bell 412s. Other features possessed by the Bell 412EPI are aautomatic engine start with temperaturee limiting features and full authority digital engine control. Therefore we need a tool that is able to facilitate the process of moving helicopters both from the shelter and from the garage. The tool is a moto tug designed by using a remote control as a tool. In addition, a wheel that will facilitate the movement of the moto tug itself is also needed, namely the mecanum wheel. Mecanum wheel has the accuracy of time effectiveness and flexibility of movement in determining the target angle quickly and precisely. Keywords: Helikopter Bell 412 EPI, Remote Control, Mecanum Wheel. Abstrak: Perkembangan dalam dunia teknologi sangat berkembang terutama dalam bidang militer. Hal ini dibuktikan dengan pada semakin meningkatnyaa alutsista yang bermacam-macam dan semakin modern. semua negara berlomba-berlomba memperkuat militernya, persiangan militer ini sudah ada sejak jaman kerajaann dengan tujuan sebagai pengembangan teknologi yang didorong oleh keinginan dan kebutuhan untuk memberikan rasa aman tehadap negaranya. Perkembang teknologi ini tidak hanya untuk persenjataan militer tetapi dalam dunia penerbangan militer juga membutuhkan alat yang dapat digunakan sebagai alat bantu dalam proses pemidahan helikopter khususnya helikopter Bell 412EPI. Helikopter Bell 412EPI merupakan helikopter milik dari Tentara Nasional Indonesia khususnya milik dari Penerbang Angkatan Darat. Bell 412EPI ini mempunyai tenaga lebih kuat dan avionik Bell 412EPI sudah menggunakan full glass cockpit. Helikopter Bell 412EPI adalah alutsista yang memiliki kemampuan mengangkut 15 Personil dan 1 orang pilott dan 14 penumpang. Helikopter jenis ini dilengkapi dengan mesinn Pratt & Whitney PT6T-9 Twin Pac, dengan tenaga take-off 15 persen lebih besar dari Bell 412 lainnya. Fitur lain yang dimiliki oleh Bell 412EPI ini adalah automatic engine start with temperature limiting features dan full authority digital engine control. Oleh karena itu dibutuhkan alat yang mampu mempermudah dalam proses pemindahan helikopter baik dari shelter maupun dari garasi. Alat tersebut adalah moto tug yang dirancang dengan menggunakan remote control sebagai alat bantu. Selain itu juga dibutuhkan roda yang akan mempermudah pergerakan moto tug itu sendiri yakni mecanum wheel. Mecanum wheel memiliki ketepatan efektifitas waktu dan fleksibilitas gerakan dalam menentukan target sudut dengan cepat dan tepat. Kata kunci: Helikopter Bell 412 EPI, Remote Control, Mecanum Wheel.